Activity of oil companies of Iraq and their role in the world economy - I. M. M. Mohammed; V. Pizengolts (Управление)
Сurrently, oil market remains one of the most demanded types of energy resources, the trade of which can be called the most important element of modern world economic relations.The global market for oil and oil products is characterized by high volatility, which requires the development of various strategies for insuring financial losses. Futures contracts are one of the main market financial risk management tools. Companies face the challenge of choosing the optimal hedging strategy. Will this strategy be used solely to hedge prices or will it become part of a wider market strategy.Another specific feature of the oil market is the participation of foreign companies in the exploration of oil fields in developing countries. Since the Iraqi oil market is currently in dire need of investment in technological infrastructure, the problem of attracting and operating foreign companies is also very topical for Iraq, and such relations themselves are also unstable and are influenced by many internal and external factors. The global energy sector is undergoing fundamental changes. At the same time, Iraq today has the most favorable opportunities for solving its economic problems, both shortterm and long-term. Iraq has a huge oil potential, largely unrealized, while possessing significant explored and undiscovered reserves. However, the oil and gas industry in Iraq requires the restoration and achievement of a stable export flow after the crisis period for it. Moreover, refineries need modernization, which requires significant financial costs.